Effect of long-term orientation on voluntary security actions. (11th March 2019) - Aurigemma, Salvatore; Mattson, Thomas
Abstract : Purpose: This paper aims to examine the impact an individual's long-term orientation (a cultural dimension) has on their attitude, behavioral intention and actual voluntary security actions taken in the context of the dangers related to poor account access management. Design/methodology/approach: The paper relied upon survey data and actual usage information from a culturally diverse sample of 227 individuals who were introduced to the specific security problem and the accepted solution of using a password manager application. Findings: The paper provides empirical evidence that the effect of positive attitudes increased when individuals were more long-term oriented, but the effect was reversed for average/negative attitudes toward the voluntary security behavior. Furthermore, participants with high long-term orientation and strong positive attitudes toward the security action actually adopted password manager applications 57 per cent more than the average adoption rate across the sample. Research limitations/implications: Due to the research approach (survey data), security context and sample population, the research results may lack generalizability. Practical implications: The findings suggest that security awareness messaging and training should account for differences in long-term orientation of the target audience and integrate the distinctly different types of messages that have been shown to improve an individual's participation in voluntary security actions. Originality/value: The paper addresses previous research calls for examining possible cultural differences that impact security behaviors and is the only study that has focused on the impact of long-term orientation, specifically on voluntary security actions.